2012
DOI: 10.1007/s11249-011-9905-4
|View full text |Cite
|
Sign up to set email alerts
|

Can Confinement-Induced Variations in the Viscous Dissipation be Measured?

Abstract: Liquids confined to molecular scales become anisotropic and often show pronounced self-organization such as layering. Although this effect is well accepted, it is still debated if confinement induces measurable changes of viscous friction. We use molecular dynamics to address this issue by simulating a Lennard-Jones liquid confined between a solid cylinder and an atomically smooth surface. The simulations reproduce the well-established variations of normal force, density, and diffusivity with the distance betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Caution should however be exerted when comparing AFM and the MD results since the MD simulations presented here do not take into account the fact that the interfacial liquid is effectively confined between the calcite surface and the AFM tip under typical imaging conditions. Recent MD simulation studies have shown that under confinement, the liquid can exhibit substantial changes in its viscoelastic properties and molecular dynamics, 57 and induce ion-specific structures. 58 The good correspondence between the trends derived from AFM and the present MD simulations results suggests that AFM can nevertheless capture the main features of the 'non-confined' interface.…”
Section: Discussionmentioning
confidence: 99%
“…Caution should however be exerted when comparing AFM and the MD results since the MD simulations presented here do not take into account the fact that the interfacial liquid is effectively confined between the calcite surface and the AFM tip under typical imaging conditions. Recent MD simulation studies have shown that under confinement, the liquid can exhibit substantial changes in its viscoelastic properties and molecular dynamics, 57 and induce ion-specific structures. 58 The good correspondence between the trends derived from AFM and the present MD simulations results suggests that AFM can nevertheless capture the main features of the 'non-confined' interface.…”
Section: Discussionmentioning
confidence: 99%
“…Whether that scenario also extends to the much larger tipsubstrate separations studied here is not clear. At larger separations, thermal fluctuations as well as the tip geometry on a larger scale may lead to increased disorder [68][69][70] and, thus, prevent the crystalline arrangement found at smaller separations.…”
Section: E Solvation Force and Distance-dependent Dissipationmentioning
confidence: 99%
“…It shows a reasonably constant profile of the elastic modulus with the tip size. The slight increase toward higher radii may be the result of jamming of the molecules during squeeze-out more likely for larger tips [41]. However, more experimental efforts are required to pinpoint the mechanism behind it.…”
Section: Resultsmentioning
confidence: 99%